Analisis Kerusakan Bending Yang Menyebabkan Striasi Pada Material Water Wall Tube PLTU Uboh Banten 3 Lontar Unit 1 - Vendy Antono; Erlina Erlina; Rangga Dwi Prasetya (JURNAL POWERPLANT, 2015)
Steam power plant At found a component At unit 1 PLTU UBOH 3 MANUSCRIPT where there is damage in the material waterwall tube.Waterwall tube that experienced kergagalan as damage rolling, bending, causing striasi happened in the vertical on the west side.Striasi are characteristic of deformation volume.for an extended period of time this may lead to more serious damage. Given the importance waterwall tube in boiler on a power plant, so I do a medical check-up and research in the material that has received the damage waterwall tube with some testing method of analysis of other chemical composition, analysis of violent methods vickers), and analysis metalografi, SHEM and EDS where it is hoped that it can be expressed the analysis of the process was badly and the reasons why components that can be damaged and have failed.